Visualization and experimental analysis of Geyser boiling phenomena in two-phase thermosyphons. (October 2019) - Londoño Pabón, Nelson Yurako; Florez Mera, Juan Pablo; Serafin Couto Vieira, Gabriel; Barbosa Henriques Mantelli, Marcia
Highlights: The Geyser Boiling Phenomenon (GBP) in a two-phase closed thermosyphon was studied. A new phenomenological description and explanation for GBP was presented. A glass thermosyphon with punctual heating was used to favor the bubble tracking. Bubbles with diameter smaller than the involucre's inner diameter can provoke GBP. A new criterion to differentiate the GBP from other boiling regimes was proposed. Abstract: The Geyser Boiling Phenomenon (GBP) is commonly present in two-phase closed thermosyphon operation. It is characterized by the violent formation of a vapor bubble at the beginning of each intermittent boiling cycle. Given the nature of this type of boiling, the thermal performance of the thermosyphon is reduced and unwanted vibrations are perceived. In this work, the GBP was experimentally studied. A test bench comprised of a glass thermosyphon with a punctual heater was designed to favor the nucleation of a single bubble in a predetermined location. A high-speed camera allowed the qualitative analysis of bubble formation and sensors installed inside the thermosyphon allowed for the quantitative characterization of the phenomena. The analysis presented is concentrated on the bubble nucleation, growth and burst. The mechanisms that act during its formation are theorized. The reasons for the intensity of the bubble burst are presented, as well as a criterion to differentiate GBP from other kinds of boiling.